Stress reduction and psychological therapy for IBS: a scoping review - Fernandes, Anjali J. T.; Farrell, Anna L.; Naveh, Sara V.; Chakraborty, Subhankar (Frontiers in Gastroenterology, 2024)
IntroductionIrritable Bowel Syndrome (IBS) is a highly prevalent functional gastrointestinal disease that is commonly associated with psychological comorbidities and maladaptive thought patterns. Previous studies report psychological therapies such as cognitive behavioral therapy (CBT) and gut-directed therapy (GDP) improve IBS symptom management and quality of life. This review seeks to understand the effectiveness of various psychotherapies across delivery methods for patients with irritable bowel syndrome.MethodsA scoping literature review of PubMed articles highlighting psychological and stress reduction treatments for IBS was conducted. 120 studies were included in the title and abstract screening. 32 studies were selected for full text review. Primary and secondary research studies that investigated the benefit of psychological therapies focusing on stress reduction and cognitive therapies for patients with gastrointestinal condition’s symptom relief met inclusion criteria for the review. 12 studies were selected for inclusion.ResultsAll 12 reviewed studies reported statistically significant improvements in IBS symptoms with psychological therapies. 8 studies also addressed quality of life and reported statistically significant improvement in intervention groups. 3 studies demonstrated persistent improvement after 12 months. 2 studies compared different types of psychotherapies and reported improvements compared to control groups but no significant differences between psychotherapies. 6 studies that compared face to face therapy with minimal contact or telephone therapy showed no difference in clinical outcomes.DiscussionPsychological therapies demonstrate reported statistically significant improvements in IBS symptoms and patient quality of life with no reported statistically significant difference across forms of healthcare delivery. Most improvements reportedly persist long-term. Further research with a broader demographic base is needed to assess the economic costs of psychological therapies and their implications for underserved communities.